Optimization design of structure invulnerability for air defense multiple sensor network - Cheng-yu SUN; Mao-xing SHEN; Hao SHENG; Jin-ke XIAO (Tongxin xuebao)
To improve the invulnerability of air defense multiple sensor network,its topological structure optimization model was established with the constraint of network node’s degree and network connectivity,combined with the total sum of network’s natural connectivity for attack strategy as object function.Then,solving steps of the model were designed based on improve artificial immune algorithm to solve the model.In order to improve the searching efficiency of the algorithm,new steps of immune review and antibody correction were designed to increase the number of effective antibodies in population.Simulation and results prove rationality of the model and feasibility of the modified artificial immune algorithm,optimization based on the index of total natural connectivity for attack strategy can improve the invulnerability of air defense multiple sensor network.